Climate Change SOS: Addressing Climate Impacts within a Climate Change Spiral of Silence. Issue 12 (2nd December 2022) - Gurney, Rachel M.; Dunlap, Riley E.; Caniglia, Beth Schaefer
Abstract: This study uncovers the dynamics that exist among key government officials working to address impacts of climate variability and change within a hostile socio-political setting. Through qualitative analysis of interviews with Oklahoma government officials, this study finds evidence of a climate change spiral of silence impacting key government decision-making processes through the suppression of climate change discourse and science. We argue that settings hostile toward climate action (where there is pervasive skepticism/denial of anthropogenic climate change and opposition to climate mitigations/adaptation policies) are primed for normative dynamics that reinforce a climate change spiral of silence.